2015
DOI: 10.1016/j.rsci.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Different Aluminum Tolerance among Indica, Japonica and Hybrid Rice Varieties

Abstract: Hydroponic cultures were conducted to compare the aluminum (Al) tolerance among different rice (Oryza sativa L.) varieties, including indica, japonica and their hybrids. The results showed that the root growth of rice plant was inhibited in different degrees among Al treated varieties. The Al tolerance observed through relative root elongation indicated that five japonica varieties including Longjing 9, Dharial, LGC 1, Ribenyou and Koshihikari were relatively more tolerant than indica varieties. Most indica va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Small Al concentrations (micromolar) can inhibit root elongation in minutes or hours, inhibiting the water and nutrient uptake, resulting in reduced growth and yield (MA & FURUKAWA, 2003;RAHMAN et al, 2018). Since roots are strongly affected by Al, many reports have shown the evaluation of traits related to the growth of the root system (CHANG et al, 2015). Here, to understand the Al toxicity effects on rice Brazilian genotypes, we evaluated the root length trait in BR-IRGA 410, BRS Curinga, IAS 12-9 Formosa and Farroupilha genotypes in response to 14mg L -1 of Al during 96 hours (Figure 1).…”
Section: Results and Discussion Farroupilha Roots Are Less Affected By Aluminum Excessmentioning
confidence: 99%
See 1 more Smart Citation
“…Small Al concentrations (micromolar) can inhibit root elongation in minutes or hours, inhibiting the water and nutrient uptake, resulting in reduced growth and yield (MA & FURUKAWA, 2003;RAHMAN et al, 2018). Since roots are strongly affected by Al, many reports have shown the evaluation of traits related to the growth of the root system (CHANG et al, 2015). Here, to understand the Al toxicity effects on rice Brazilian genotypes, we evaluated the root length trait in BR-IRGA 410, BRS Curinga, IAS 12-9 Formosa and Farroupilha genotypes in response to 14mg L -1 of Al during 96 hours (Figure 1).…”
Section: Results and Discussion Farroupilha Roots Are Less Affected By Aluminum Excessmentioning
confidence: 99%
“…In acid soils, Al is solubilized to its ionic form (Al 3+ ), which is toxic to the plants (FOY, 1988;ARENHART et al, 2014). The presence of Al in soil solution quickly inhibits the root growth as well as water and nutrient uptake by the plant, resulting in a significant reduction in the crop production under these conditions (CHANG et al, 2015). It is estimated that acidic soils comprise 40 and 50% of the world's arable soil (KOCHIAN et al, 2015;RAHMAN et al, 2018).…”
mentioning
confidence: 99%
“…Moreover, the genotype difference in shoot production suggested that screening cultivars could offer options to boost production while enhancing co-benefits in rice agriculture (Noguera et al, 2011 ). The two Japonica rice cultivars of W7 and NP were widely used as mother plant in rice breeding and as a model plant in rice research in China and Asian countries (Gao et al, 2011 ; Chang et al, 2015 ), and cultivar innovation by germplasm had been mostly with yield improvement by <15% (Peng et al, 2008 ). Thus, there could be a great potential to use a sound combination of optimal crop cultivar with biochar application in crop production improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble Al ions, especially Al +3 , are released at the soil exchange complex in soils with pH values lower than 5. These ions lead to root growth inhibition, resulting in decreased water and nutrient uptake and plant growth and changes in dry matter partitioning between the root and shoot (Chang et al, 2015;Eekhout et al, 2017). For this reason, Al is considered one of the primary abiotic factors that limit agricultural productivity (Ritchey et al, 1995;Ryan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%